A Study of High School Teachers Views on Professional Values in Terms of Different Variables - BAKİOĞLU, AYŞEN (ANI PUBLISHING, 2017)
The purpose of this study is to analyse the factors affecting viewpoints of high school teachers towards professional values. The research which consists of quantitative and qualitative research methods has the characteristics of mixed survey model. Teachers working in public secondary schools located in the Anatolian side of Istanbul form the target universe of the research. Kadikoy, Umraniye and Sultanbeyli districts and stratified sampling method were selected to form the sample. The answers given to the research questionnaire by 461 teachers working in secondary schools in the aforementioned districts were taken into consideration. For the qualitative stage of the study, purposive sampling was chosen and maximum variety and snowball sampling methods were used as the strategy. 30 teachers working in the high schools in the same districts were involved in the qualitative stage of the study. In order to determine the opinions of the participants in relation to professional values according to independent variables, t-Test and Anova were applied. In the qualitative stage of the study, the participants were interviewed and interview notes were analysed with content analysis. The schools were divided into three groups: red, yellow and green, by determining years of seniority of the teachers and the professional values they possessed. It was found out that professional values of female teachers had been higher than male teachers. It was identified that teachers having post-graduate education had higher professional values comparing with the ones having a bachelor's degree.
Keywords: Values; teachers' professional values; red schools; yellow schools; green schools